Удосконалення системи обслуговування асинхронних двигунів - Полковніченко, Д. В.; Москвіна, І. І. (НТУ "ХПІ", 2014)
Виконано аналіз шляхів переходу від планово-попереджувальних ремонтів до системи обслуговування за фактичним станом короткозамкнених асинхронних двигунів за рахунок застосування методів діагностики, що дозволяють оцінити їх технічний стан в робочих режим. З цією метою запропоновано використовувати комплексний критерій справності, який визначається на підставі контролю несиметрії фазних струмів статора і кута нахилу механічної характеристики

The researches of opportunities of an estimation of a technical condition of asynchronous electric motors with short-circuited rotors after repair are carried out. The analysis of the transition from a planned preventive maintenance system to service the actual condition of short induction motors through the use of diagnostic methods to assess their technical condition in the working mode. To this end, proposed to use complex criteria serviceability, which is determined based on the control of asymmetry stator phase currents and the angle of inclination of the mechanical properties. The results of a research on computer of sensitivity of the given criterion for various defects of windings of the asynchronous electric motor are given
Improvement of system service of induction motors
Keywords: асинхронні електродвигуни; технічне обслуговування; обслуговування за фактичним станом; діагностика; критерій; induction motors; preventive maintenance; maintenance of the actual condition; diagnosis